Treatment decision-making and treatment experiences in men with metastatic castration-resistant prostate cancer - Sandra Doveson; Per Fransson; Lena Axelsson; Agneta Wennman-Larsen (Acta Oncologica)
Background and purpose: For the most advanced stage of metastatic castration-resistant prostate cancer (mCRPC), several life-prolonging treatments have become available over the past decade. Treatment decision-making (TDM) and experiences in this phase are yet to be studied. Hence, this study aimed to describe men’s satisfaction with TDM and treatment experiences during the first 12 months of a life-prolonging treatment of mCRPC.